Implementasi Nilai-Nilai Organisasi untuk Meningkatkan Kinerja Lembaga Publik - Fitriyani, Indah; Amanatun Suryani, Dewi (Policy, Law and Political Research Center, 2025)
The application of organizational values is important in human capital management in order to drive performance to be more competitive in achieving company goals. This study aims to determine the implementation of the 5C values (Commitment, Competence, Communicative, Collaborative, Customer Focus) and identify the supporting and inhibiting factors. The research method used is descriptive qualitative. Data collection was conducted through observation, documentation, and interviews. The results show that the implementation of commitment and competence values has been optimal, as indicated by employee responsibility and capability. However, the values of communication, collaboration, and customer focus are still not optimal due to the awkwardness and challenges faced by each individual. The supporting factors for the implementation of the 5C values are SOPs, environment, spirituality, discipline, and concern, while the inhibiting factors are length of service and generational characteristics. Morning briefings are effective in building communication and need to be maintained. Efforts to improve the implementation of values include performance appraisals, rewards or sanctions, internal company training, and periodic evaluations, which are expected to have a positive impact on work culture and bridge the gap between employees and the company in improving future performance.